Faith in the year of faith. Ratzinger’s proposal - Pablo Blanco Sarto (Polonia Sacra)
J. Ratzinger/Benedict XVI as a pope and author of the idea promulgating the Year of Faith is presented in the paper with his concept of faith. The striking element of Ratzinger’s theology is a personal approach to faith. Faith as an encounter triggering conversion is a fully positive and existencial experience of God, who engages the whole person and personality (unitotality of faith), the reason and love. This attitude of faith builds human praxis and shapes interpersonal relations. Here comes the phenomenon of the Church, which the Pope treats as a source and place of faith, especially with reference to liturgy, owing to which the true relation with the Trune God is established and developed.